تأثير تدريب المهارات النفسية على مستوى الأداء الفني للسباحين من ذوي الاحتياجات الخاصة - حسنين، محمد عبدالكريم نبهان; مقلد، محمد عبدالحميد طه; محمد، هشام عمر; محمد، لمياء فؤاد (جامعة بنها - كلية التربية الرياضية للبنين, 2023)
يهدف البحث إلى التعرف على تأثير تدريب المهارات النفسية ومستوى الأداء الفني للسباحين من ذوي الاحتياجات الخاصة، واستخدمت الباحثة المنهج التجريبي التصميم التجريبي (ذو القياس القبلي والبعدي) لمجموعة واحدة تجريبية وذلك لملائمته لطبيعة هذه الدراسة، ويتمثل مجتمع البحث في سباحين ٥٠ متر حرة من ذوي الاحتياجات الخاصة بمحافظة (القاهرة)، وعددهم (۷۸) سباح، وأشارت أهم النتائج إلى: ۱. إن برنامج المهارات النفسية له تأثير إيجابي دال إحصائيا لصالح القياس البعدي للمجموعة التجريبية قيد البحث هل توجد فروق ذات دلالة إحصائية بين متوسطي القياسيين القبلي والبعدي للعينة قيد البحث لصالح القياس البعدي للمهارات النفسية للسباحين من ذوي الاحتياجات الخاصة قيد البحث. ٢. إنه هناك فروق ذات دلالة إحصائية بين متوسطي القياسيين القبلي والبعدي للعينة قيد البحث لصالح القياس البعدي لمستوى الأداء الفني " سباحة ٥٠ متر حرة " للسباحين من ذوي الاحتياجات الخاصة قيد البحث. 3- إنه هناك فروق ذات دلالة إحصائية بين متوسطي القياسيين القبلي والبعدي للعينة قيد البحث لصالح القياس البعدي في تحسين للمستوى الرقمي " لسباحة ٥٠ متر حرة " للسباحين من ذوي الاحتياجات الخاصة قيد البحث. The research aims to identify the effect of training psychological skills and the level of technical performance of swimmers with special needs, and the researcher used the experimental approach experimental design (with pre and post measurement) for one experimental group, due to its suitability to the nature of this study, and the research community consists of 50-meter freestyle swimmers with The special needs of (Cairo) governorate, and their number is (78) swimmers, and the most important results indicated: 1.The psychological skills program has a statistically significant positive effect in favor of the post-measurement of the experimental group under study. Are there any statistically significant differences between the mean of the pre and post-standards of the sample under study in favor of the post-measurement of the psychological skills of swimmers with special needs under study. 2. There are statistically significant differences between the averages of the pre and post standards of the sample under study in favor of the post measurement of the level of technical performance "50-meter freestyle swimming" for swimmers with special needs under study. 3. There are statistically significant differences between the averages of the pre and post measurements of the sample under study in favor of the post measurement in improving the numerical level of "50-meter freestyle swimming" for swimmers with special needs under study.
Keywords: البرامج التدريبية -- المهارات النفسية -- رياضة السباحة -- الأداء الفني -- ذوي الاحتياجات الخاصة